Over 5 million sub-Saharan African households benefit from improved drought tolerant maize varieties - CGIAR Research Program on Maize (2019)
The Drought Tolerant Maize for Africa project, followed by the Stress Tolerant Maize for Africa project, gave smallholder farmers in 13 countries access to improved drought and stress tolerant maize varieties. Over 200 distinct drought tolerant maize hybrids and open pollinated varieties were released throughout both projects’ lifetime (12 years), of which 54,000 tons of certified DT maize seed was produced, benefiting an estimated 5.4 million households – or 43 million people – who planted them on 2.75M ha. With STMA closing in early 2020, a follow-up project will continue to deliver and track impacts.